Business proposal for improving the supply chain management in order to open a new distribution channel for SuCarne Inc. - Mora Torosine, Ricardo Rubén (2017)
This project involves the improvement of the supply chain management (SCM) of SuCarne Inc. based on the Scor Model that enhance its value chain linked to external actors. The commitment of this proposal will be carried out through a new distribution channel as e-tailing, which allows the company to be integrated directly to the consumer. The research design is non-experimental applying a mixed approach as quantitative for demonstrating the financial indicators -statistical method and qualitative to collect interviews and qualify suppliers. The sampling method is non-probabilistic-purposive by focusing on a specific market segment as 13 neighborhoods from Via a la Costa Km 9,8 until 21,5. The main objective of the study embraces a business proposal to ensure the adjustment made on the SCM by developing a new portfolio of products through the modification of the organizational business model from B2B to B2C to become specialist on grill meat steaks. The results obtained are positive that encompasses an IRR of 36,34 % and a VPN of $33.811,14 for a WACC discount rate of 22,58% calculated by an average of the Beta coefficient, market return, project return on the three scenarios and the loan financial entity rate.